The world : a brief introduction - Haass, Richard (Penguin Press, 2020)
"This book is designed to provide readers with the background and building blocks they need in order to answer for themselves the critical questions about what is taking place around the world and why. It explains what makes each region of the world tick, the many challenges globalization presents, and the most influential countries, events, and ideas. Its aim is to help readers become more informed, discerning citizens, better able to arrive at sound, independent judgments and less vulnerable to being misled"--